We the leader : build a team of equals who all lead and follow to drive creativity and innovation - Spahn, Jeffrey (McGraw Hill, 2022)
"We the Leader represents a seismic shift in the evolution of leadership theory and practice. By implementing this innovative practice built on diversity, equity, inclusion, any organization can drive consistent winning results with ingenuity and speed. Leadership is collective art. That's the guiding principle behind Jeffrey Spahn's approach to creating sustained innovation within organizations. Spahn has guided myriad companies toward a more solid leadership foundation, and in this eye-opening guide, he shares his most powerful wisdom and shows you how to apply it to your own business. Moving beyond the traditional model of top-down leadership, Spahn has created a foundation for an organizational culture that benefits from collective energy, curious conviction, and solid, actionable goals. You'll find enlightening guidance on such principles as: Collective flow-being driven by an energy beyond the limits of individuals Panarchy-navigating the emerging terrain of collective leadership Simultaneity-accessing collective flow by leading and following in the same action Consilience-embracing opposing viewpoints as an opportunity to make a difference through differences Filled with case studies of Spahn's work with industry-leading companies and an effective decision-making process rooted in these principles, We the Leader represents the next step in the evolution of leadership-a fresh-eyed new way forward for your organization"--